A sala de aula em cena: uma pesquisa em ensino do teatro a partir da experiência docente - Silva, Gisele Carvalho da (2013)
At first moment we present a reflection about the history of theater and later a contextualization of didactic movements oriented to scenic arts. Through at the constant dialogue with authors of areas involving education, theatre, corporeality and music was possible analyzing, develop and criticize a education work under my responsibility involving fourteen classes. At the second moment will occur a critical self about the quality of theater classes his contents and methodologies. The technique will be at side of the emotion and together develop skills aimed at tracing paths for theater developed at a classroom of a especific private school in Natal-RN. At the third moment one class is chosen for analyze of the academic research and many experiments happen after this decision, initiated and sensitized through of the music with a significant look at the corporeality and prioritizing the theater as content in ninth grade - elementary school two. At the conclusion is possible see that learning is mutual and the theater can become life routine as well as the arts in general and when all arts will be regularized into the national educational system for public and private schools we will have more susceptible humans and more intellectual capacity